Evaluation of Queue Management System (QMS) Use in Chest X-Ray for Tuberculosis Screening: A Case Study - Nwaiwu, Victor Chigbundu; Das, Sreemoy Kanti (Indian Journal of Radiology and Imaging, 2025)
Tuberculosis (TB) remains a threat to public health globally and is one of the top infectious killer diseases in Africa and Asia. The government and international partners have strategically intervened by cascading chest radiography (CXR) to identify, manage, and monitor treatments outcomes. However, patient have reportedly been dissatisfied with the quality of CXR screening services provided, raising complains that spans across quality of care, waiting times, communication levels, staff attitudes, and treatment outcomes.Coming at this present time when the major focus in health care is on improving patients' care and experience, this study aims to ascertain the performance of queue management system (QMS) use for CXR-TB screening in Nigeria as well as its acceptability; adopting quantitative research design.Questionnaires were administered face-to-face to the three categories of respondents (radiographers, radiology assistants, and patients) who meet the specific set of inclusion criteria, following a brief explanation about the research aim. Consent was gotten by way of a signed consent form and ethical approval obtained. A Likert 5-point scale was utilized in analyzing the responses, undergoing descriptive statistics using SPSS (version 25) software.QMS is extremely useful in workflow, accuracy, communication, combatting work stress, and maintaining privacy, but with accompanying occasional technical challenges. A remarkable preference for QMS to manual in CXR-TB screening was noted among all research subjects, with strong level of agreement (close mean values of 4.06, 3.81, 3.91; standard deviation of 0.70, 0.73, 0.60).Findings from this study uncover the vital role the QMS plays in improving the quality of CXR-TB screening services, demonstrating great acceptability.
Keywords: queue management system; chest X-ray; tuberculosis screening; queueing systems